Pengaruh Harga Emas Global Dan Nilai Tukar Rupiah/Dollar Amerika Terhadap Harga Saham PT J Resources Asia Pasifik Tbk Pada Tahun 2020-2024 - Mu'min, Ali; Syafira Ramadhan; Fadiah Toon; Moh. Taufik Saidul Akbar (RITMA: Journal of Islamic Integrated Research, Science, and Community, 2025)
This study aims to analyse the effect of global gold prices and the rupiah/US dollar exchange rate on the share price of PT J Resources Asia Pasifik Tbk during the period 2020-2024. The share price of PT J Resources Tbk, as a gold mining company, does not move in line with macroeconomic sentiment, which should be positive. The method used is quantitative with monthly time-series secondary data (N=60) processed using multiple linear regression. The F-test results show that GOLD and IDR have a simultaneous significant effect. The t-test results found that (1) Global Gold Prices have a positive and significant effect, in line with the hypothesis. (2) The Rupiah Exchange Rate has a negative and significant effect, which rejects the initial theoretical hypothesis. The Adjusted R Square value was only 30.0%, proving that 70.0% of the variation in PSAB share prices was dominated by internal factors outside the research variables. In conclusion, the market responded negatively to the weakening of the Rupiah, indicating investor concerns about the foreign currency debt risk of companies.